Regulasi Surat Pertanggungjawaban Mutlak Perspektif Maslahah Mursalah (Studi Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jember) - Hanifah A’inur Rohmah (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to examine public perceptions of the regulation on the Statement of Absolute Responsibility (SPTJM), analyze the factors influencing its use, and review the regulation from the perspective of maslahah mursalah. The SPTJM, issued by the Ministry of Home Affairs, serves as an administrative solution for couples without an official marriage certificate. However, it is often used by young couples to fulfill administrative requirements without registering their marriage at the Office of Religious Affairs (KUA). This research employs an empirical juridical approach, combining sociological and statutory approaches. Data were collected through interviews and document analysis, then analyzed descriptively to illustrate the social phenomena and legal implications surrounding the use of SPTJM. The findings reveal that public and institutional perceptions of SPTJM vary. The Civil Registry Office (Dispenduk) views it as an administrative solution to overcome document limitations, while the KUA considers it a factor that decreases public awareness of the legal requirement to register marriages formally. The use of SPTJM is prevalent in issuing birth certificates for children from unregistered marriages, driven by the ease of procedure, high cost of marriage legalization (isbat nikah), and local cultural beliefs that unregistered (siri) marriages are religiously valid. From the perspective of maslahah mursalah, SPTJM provides short-term administrative benefits categorized as hajiyyat (secondary benefits); however, it fails to fulfill the higher objective of Islamic law, particularly in safeguarding lineage (hifdz al-nasl).